The potential use of plant-derived saponins as a phytobiotic additive in poultry feed for production and health advancement: a comprehensive review - Alghirani, Mohamed M.; Lim, Eric Teik Chung; Abdullah Jesse, Faez Firdaus; Sazili, Awis Qurni; Loh, Teck Chwen (Gorgan University of Agricultural Sciences and Natural Resources, 2022)
The food security of a country can be harmed if the supply and demand of poultry products are affected due to any disruptions disrupted by factors such as poor growth rates and disease outbreaks. On top of that, with regard to food safety reasons, developed countries have started to prohibit the inclusion of antibiotics in livestock feed. As a result, it is essential to seek alternative preventive substitutes for growth promotion and prophylaxis in poultry rather than depending on antibiotics. Plant extracts are one of the alternatives with anti-microbial and growth-promoting effects on poultry. Saponins have many biological and pharmacological activities like anti-carcinogenic, anti-microbial, anti-parasitic, anti-fungal, anti-inflammatory, hypocholesterolemic, immunomodulatory, and anti-oxidant properties. Because of its growth-promoting effect, immunity enhancer, and microbial capabilities, saponins from diverse sources and quantities could be used as an anti-microbial alternative to synthetic antibiotics in the broiler industry. Additionally, steroidal saponins have been commercialized as supplements for poultry, health foods for human consumption, and potential anti-cancer treatments. Therefore, the present review will critically shed light on the availability of different saponins and the influence on the production performance and immunopathology responses of poultry supplemented with different saponins extract. Information from this review will added knowledge on the usability of different saponins extracts which could be considered as a novel feed additive in the poultry industry.